Coming of age and changing institutional pathways across generations in Rwanda - Pontalti, K (2017)
This thesis offers an account of children's lived experiences in Rwanda (1930s-2016) in four key domains: kinship, education, economic transitions, and marriage. Based on historical and ethnographic fieldwork in rural and urban Rwanda from 2012 to 2014, this work explores how three generations of young people have experienced and navigated childhood and coming of age at the interface of 'traditional' and 'modern' institutional systems. Rather than focusing narrowly on 'crisis' childhoods, individual agency, or exogenous forces, as studies of young Africans and social change tend to, this work examines young people's 'everyday' actions – intentional and unintentional, individual and collective, compliant and non-compliant - and locates them within their broader historical, relational, and institutional environment. By focusing on the intensely reproductive period of childhood and coming of age, on Rwanda’s unexceptional majority rather than its exceptionally vulnerable minority, and on children’s everyday actions rather than the strategic actions of elites, this thesis shows us how children shape the institutions of childhood and marriage and, in so doing, influence how society is reproduced and changed. Theoretically, this thesis explains how children and their institutional environment are mutually constituting: it examines how and why young people experience rapid change and structural violence differently and it traces how they reproduce and change these structural conditions as they engage with institutional mechanisms in (un)intended ways. The research reveals that children in central Rwanda navigate constraints and opportunities by drawing on established kinship relationships and institutions while also opportunistically engaging with modern institutions and their actors. However, in this context of 'institutional multiplicity', traditional and modern institutional systems each need Rwanda’s young majority to reproduce their institutions over others', and as intended, to achieve their power-distributional goals. This makes children’s actions particularly consequential and demands that we redefine what political action – and political actors – look like.